Walter Lippmann : public economist - Goodwin, Craufurd D., 1934-2017 (Harvard University Press, 2014)
Walter Lippmann was the most distinguished American journalist and public philosopher of the twentieth century. But he was also something more: a public economist who helped millions of ordinary citizens make sense of the most devastating economic depression in history. Craufurd Goodwin offers a new perspective from which to view this celebrated but only partly understood icon of American letters. From 1931 to 1946 Lippmann pursued a far-ranging correspondence with leading economic thinkers: John Maynard Keynes, Lionel Robbins, Friedrich Hayek, Henry Simons, Adolf Berle, Frank Taussig, and others. Sifting through their divergent views, Lippmann formed his own ideas about economic policy during the Great Depression and shared them with a vast readership in his syndicated column, Today and Tomorrow. Unemployment, monetary and fiscal policy, and the merits and drawbacks of free markets were just a few of the issues he helped explain to the public, at a time when professional economists who were also skilled at translating abstract concepts for a lay audience had yet to come on the scene. After World War II Lippmann focused on foreign affairs but revisited economic policy when he saw threats to liberal democracy. In addition to pointing out the significance of the Marshall Plan and the World Bank, he addressed the emerging challenge of inflation and what he called "the riddle of the Sphinx": whether price stability and full employment could be achieved in an economy with strong unions